The Impact of Wet Cupping on Sleep Quality in Healthy People at Medan City Health Clinic - Nasution, Sharlini Desfika (Journal of Islamic Medicine, 2025)
Background: Sleep quality is an essential need for health and body recovery. Sleep disorders are a serious health problem with a global prevalence reaching 19.1% according to WHO (2020). In Indonesia, the prevalence of sleep disorders among individuals aged ≥15 years is reported at 11.0% for clinically significant insomnia symptoms and 33.3% for sub-clinical insomnia. Cupping therapy as a complementary treatment has been known since ancient civilization and is recommended in Islam, but research on its impact on sleep quality is still limited. Objective:   To determine the impact of wet cupping on sleep quality in healthy people at a health clinic in Medan City. Methods:    This quantitative study used a descriptive analytical design with a one-group pretest-posttest pre-experimental approach, involving 36 respondents at the Medan City Cupping Health Clinic. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), and data were analyzed using the Wilcoxon Signed-Rank test. Results:  Wet cupping intervention resulted in significant improvements in sleep quality. The results of the Wilcoxon Signed-Rank Test showed a significant difference between sleep quality before and after the intervention (p-value = 0.000) with a decrease in the average PSQI score from 9.428 to 5.167. Conclusion: Wet cupping has been proven effective in improving sleep quality in healthy people and can be an alternative non-pharmacological treatment to overcome sleep disorders and improve quality of life.